Label-free electrochemical impedance detection of kinase and phosphatase activities using carbon nanofiber nanoelectrode arrays - Li, Yi Fen; Syed, Lateef; Liu, Jianwei; Hua, Duy H.; Li, Jun (My University, 2012)
We demonstrate the feasibility of a label-free electrochemical method to detect the kinetics of phosphorylation and dephosphorylation of surface-attached peptides catalyzed by kinase and phosphatase, respectively. The peptides with a sequence specific to c-Src tyrosine kinase and protein tyrosine phosphatase 1B (PTP1B) were first validated with ELISA-based protein tyrosine kinase assay and then functionalized on vertically aligned carbon nanofiber (VACNF) nanoelectrode arrays (NEAs). Real-time electrochemical impedance spectroscopy (REIS) measurements showed reversible impedance changes upon the addition of c-Src kinase and PTP1B phosphatase. Only a small and unreliable impedance variation was observed during the peptide phosphorylation, but a large and fast impedance decrease was observed during the peptide dephosphorylation at different PTP1B concentrations. The REIS data of dephosphorylation displayed a well-defined exponential decay following the Michaelis–Menten heterogeneous enzymatic model with a specific constant, k[subscript]c[subscript]a[subscript]t/K[subscript]m, of (2.1 ± 0.1) × 10[superscript]7 M[superscript]−[superscript]1 s[superscript]−[superscript]1. Consistent values of the specific constant was measured at PTP1B concentration varying from 1.2 to 2.4 nM with the corresponding electrochemical signal decay constant varying from 38.5 to 19.1 s. This electrochemical method can be potentially used as a label-free method for profiling enzyme activities in fast reactions.
Keywords: Real-time electrochemical impedance spectroscopy; Phosphorylation; Dephosphorylation; Heterogeneous enzyme kinetics; Vertically aligned carbon nanofibers; c-Src tyrosine kinase; Protein tyrosine phosphatase 1B; Nanoelectrode array